Nos caminhos do progresso, nas veredas da modernização: representações da cidade de Sousa-PB - Dário, Rafaela Pereira (2012)
This dissertation aims to demonstrate the ways a regular backcountry - The magazine letters Hinterland - represented the city of Sousa in his first two phases of movement were from 1951 to 1963. Taking into consideration the role that social media takes, we dare say that the magazine's editors anchored in the social place that assumed, extrapolated content literarário the same and from articles and notes stamped in a political magazine where a lot of criticism and claims was evidenced. Such criticisms are made because the reality of the nation at that time to be quite different from the experienced in the early twentieth century, as well as most Brazilian cities, Sousa undertook important material gains during that period that gave an air of modern. During the 1930s, the city continued to grow, and this time, the commercial and industrial activities have been strengthened at the expense of infrastructure improvements such as street paving, improvements in the system of water supply and electric light, street cleaning, etc.. We can say that the claims made by the literate elite who composed letters Hinterland were based obseravação of "precarious" infrastructure of the city, which subsisted since the beginning of the century and that kept in their view, that Sousa alçasse fly higher toward development. From the year 1955, the city began to be represented otherwise since the municipal government decided to follow developmentalism Juscelinian investing and infrastructure in an attempt to boost economic growth Sousa. This study adds to the research line regional history of the Graduate Program in the History of the Federal University of Paraiba with a major in History and Historical Culture.